Constructing rajpootana Rajasthan - "Hooja, Rakesh.(ed.)" (Jaipur, 2010)
The story of Rajasthan is interesting, not only from a linear historical standpoint, but also from a cultural, sociological, and social change perspective. This collection of essays provides a multi-faceted look at Rajasthan and the modern-day capital of Jaipur. The book is a potpourri that explores Rajasthan's present and past.
Keywords: Rajasthan-History